2012
DOI: 10.1186/1471-2164-13-527
|View full text |Cite
|
Sign up to set email alerts
|

Annotated genetic linkage maps of Pinus pinaster Ait. from a Central Spain population using microsatellite and gene based markers

Abstract: BackgroundPinus pinaster Ait. is a major resin producing species in Spain. Genetic linkage mapping can facilitate marker-assisted selection (MAS) through the identification of Quantitative Trait Loci and selection of allelic variants of interest in breeding populations. In this study, we report annotated genetic linkage maps for two individuals (C14 and C15) belonging to a breeding program aiming to increase resin production. We use different types of DNA markers, including last-generation molecular markers.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 88 publications
1
16
0
Order By: Relevance
“…Synteny and colinearity were highly conserved when compared with 654 common markers with previous studies [20, 81, 82]. Only three discrepancies were found that supposed just a 0.46% over all the common markers analyzed: Contig CT577280 was mapped in LG 7 and LG 4 in two of three obtained maps for P. pinaster in Chancerel et al [20] and it was suggested the existence of two paralogous genes for this sequence.…”
Section: Discussionmentioning
confidence: 55%
“…Synteny and colinearity were highly conserved when compared with 654 common markers with previous studies [20, 81, 82]. Only three discrepancies were found that supposed just a 0.46% over all the common markers analyzed: Contig CT577280 was mapped in LG 7 and LG 4 in two of three obtained maps for P. pinaster in Chancerel et al [20] and it was suggested the existence of two paralogous genes for this sequence.…”
Section: Discussionmentioning
confidence: 55%
“…P. pinaster originated on, and is distributed throughout, the Iberian Peninsula, from where it spread along the mountain ranges (Gil 1991), becoming diversified in numerous populations with their own genetic characteristics (González-Martínez et al 2004;Sánchez-Gómez et al 2010;de Miguel et al 2012). The different responses to climate established for the center, the Mediterranean area and the Atlantic coast of the Iberian Peninsula (Bogino and Bravo 2008;Vieira et al 2009;Rozas et al 2009;Sánchez-Salguero et al 2010;CandelPérez et al 2012), also indicate marked differences with regard to adaptation to very diverse climate conditions, which should also be considered in ecological restoration, with seeds being selected from the regions of origin (Alia et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…To corroborate that historical and demographic processes were adequately accounted for, 12 nuclear microsatellites (SSRs) distributed in 8 of the 12 linkage groups of the species (Chancerel et al 2011;de-Miguel et al 2012) were genotyped following Santos-Del-Blanco et al (2012) and references therein. However, three of them (epi6, ctg275, NZPR544) were excluded from further analyses after detecting high frequencies of null alleles, which led to significant deviations from HardyWeinberg expectations in more than half of the populations (see Table S1).…”
Section: Microsatellite Genotyping and Phylogeographic Analysesmentioning
confidence: 99%